Residual, Enrichment and Health Risk Assessment of Hexachlorocyclohexane and Dichlorodiphenyltrichloroethane in Muscle of Cultured Common Carp - Li Huang; Lei Gao; Song Wu; Peng Wang; Zhongxiang Chen; Qirui Hao; Dongli Qin; Xiaoli Huang (Foods)
Common carp (Cyprinus carpio) is extensively cultured and widely consumed in Heilongjiang Province, China. Due to the proximity of freshwater ponds to agricultural cultivated areas, these aquatic systems are inevitably influenced by the historical application of organochlorine pesticides (OCPs), due to their prolonged half-life and resistance to degradation. Gas chromatography-tandem mass spectrometry (GC-MS/MS) was utilized to quantify the levels of hexachlorocyclohexane (HCHs) and dichlorodiphenyltrichloroethane (DDTs) in the muscle tissue of cultured common carp. This study examined the enrichment characteristics of HCHs and DDTs in fish muscle, as well as their correlation with sediment and associated risk assessments. The results showed that the residual levels of HCHs and DDTs in fish muscle ranged from 0.387 μg·kg−1 to 3.418 μg·kg−1 and from 0.114 μg·kg−1 to 0.420 μg·kg−1, respectively. They were all below the maximum residue limits specified in GB 2763-2021 (HCHs: 100 μg·kg−1, DDTs: 500 μg·kg−1). The concentrations of HCHs and DDTs in sediment were found to be lower than those in muscle tissue. Notably, the concentrations of HCHs were higher than those of DDTs in both muscle and sediment. Among the HCHs, γ-HCH was the predominant residual substance, contributing a significant proportion of 42.16% to 86.47%. No significant residues of DDT derivatives were detected. A significant correlation was observed between the concentrations of HCHs and DDTs in the muscle tissue and those present in the sediment (p < 0.01). The health risk assessment indicated that both the carcinogenic and non-carcinogenic risks associated with OCPs from common carp muscle and sediment were within acceptable limits. Therefore, it was recommended to regulate fish consumption during the breeding period.